Frequency and Pattern of Presentation of Neck Lymphadenopathy in Oral Squamous Cell Carcinoma in Patients Presenting to Nishtar Hospital, Multan - Sidra Tulmuntaha, Muhammad Fishan, Asif Nazir, Muhammad Inqalab Fareed, Safoora Hashmi, Nasir Abbas, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Frequency and pattern of presentation of neck lymphadenopathy in oral squamous cell carcinoma. Study Design: Place and Duration of Study: Nishtar Institute of Dentistry Multan from 1st January 2021 to 31st December 2021. Methodology: Forty lymph nodal involvement were assed, either unilateral, bilateral and multiple or single. It was checked how many lymph nodes are involved; extra capsular spread was assessed. The findings of a histological examination of the removed tissue were obtained. Level of lymph adenopathy was measured. Results: Mean age was found to be 46.9 with minimum of 20 and maximum of 75. There were total 25(62.5%) males and 15(37.5%) females. Ten (25%) patients had lip involvement and 22(55%) had buccal mucosa, 6(15%) had gingival, 2(5%) has palate evolved. Eight (20%) were found to be having unilateral lymph node evolved while 32(80%) were found to be having bilateral evolvement. 20(50%) were having single lymph node involvement and 20 (50%) were having multiple lymph node involvement. Twenty (50%) were having <3 lymph node size and 20 (50%) were having 3-6 lymph node size. Consistency of lymph node was hard 18 (45%) and rubbery in 22 (55%). Twenty-six (65%) were having 1-3 lymph node involvement and 14 (35%) were having 5- 10 lymph node involved. Extra capsular spread was seen in 2 (5%) cases. Practical implication Conclusion: Most of cases presented of oral squamous carcinoma were stage I and stage II. Bilateral lymph nodal involvement was seen was common and buccal mucosa was commonly affected site. Keywords: Carcinoma, Oral squamous carcinoma, Lymph node, Lymph adenopathy